Analysis of The Nutritional Content and Sensory Properties of Steamed Sponge Cake Substituted Yellow Pumpkin Flour (Curcubita moschata D.) and Mung Bean Flour (Vigna radiata L.) as Alternative Snack for Teenagers - Lestari, Dina Putri (Nutrizione: Nutrition Research And Development Journal, 2023)
Nutritional problems of youth in Indonesia are still prone to occur, including inappropriate consumption patterns. Inappropriate eating behavior can have a negative impact on the nutritional status of youth, one of which is underweight. Data from the 2018 Riskesdas results, the prevalence of underweight or malnourished youth reached 16,8%. The provision of snack foods rich in nutritional content contributes to meeting calorie needs during their growth period and improving the nutritional status of youth. This study aims to determine the nutritional content and sensory properties of steamed sponge cake substituted with pumpkin flour and mung bean flour as a nutrient-dense snack that is practically consumed. This type of experimental research used a completely randomized design with three treatments and two repetitions. The formulation of steamed sponge cake is the ratio of pumpkin flour, mung bean flour, and wheat flour, namely F0 (0 : 0 : 100), F1 (15 : 35 : 50), F2 (30 : 20 : 50), F3 (45: 5 : 50). Sensory tests were carried out on 30 cunsumer panelists. Data analysis of proximate test results used descriptive analysis and sensory test results used the Kruskal Wallis test continued with the Mann Whitney test. The sensory test results showed that there were significant differences in color (p=0,000), aroma (p=0,000), texture (p=0,014), and taste (p=0,000) in the four formulas. The result of the overall sensory test that the panelists most favored was F0. F3 produces the highest nutritional content of the steamed sponge cake formula in 100 grams contains an average of 373,13 kcal of energy, 11,28 g protein, 17,85 g fat, 41,83 g carbohydrates